STUDIES ON THE PRAWN FISHERY OF COCHIN AND ALLEPPEY COAST - George, M J (Indian Journal of Fisheries, 2011)
IN the marine fisheries of the Indian coast prawns occupy an importantposition. The major portion of the marine prawn catches is from the westcoast. According to Panikkar and Menon (1955) "In certain areas, especiallyon the west coast, the catches of prawns as a group may be more than thoseof any other single group of fishes". In order to obtain a clear picture ofthe fishery along this coast detailed study has been initiated by the CentralMarine Fisheries Research Institute at a number of centres, viz., Kandla,Bombay, Mangalore, Kozhikode, Cochin (Ernakulam) and Colachel. Fromthe Ernakulam centre the middle part of Kerala coast has been coveredselecting three points, Alleppey, Chellanam and Narakkal, about 22 milesapart. Alleppey situated about 35 miles south of Cochin is one of theheaviest prawn-landing centres. Here in some months of the peak seasonthe catches at one landing centre alone has exceeded 1000 m. tons. Thepresence of mud banks, locally called "chakara" is one of the reasonsattributed to the magnitude of the prawn fishery here. Chellanam, situatedat about 14 miles south and Narakkal 8 miles north of Cochin harbour arealso prawn fishing centres.